Persepsi Mahasiswa Terhadap Mutu Internal Fakultas Ekonomi Universitas Lancang Kuning - Prama Widayat (Jurnal Penjaminan Mutu, 2020)
The Faculty of Economics, Lancang Kuning University has Management and Accounting study programs with more than 2000 students. Of course they have felt the atmosphere of lectures for several semesters with all the advantages and disadvantages possessed by the Faculty of Economics, Lancang University. For this reason, further research needs to be done to get responses from students about the internal quality of the yellow faculty of economics. because they are users of the college. It is hoped that this research will provide positive input for the faculty of Economics at Lancang Kuning University to improve all the deficiencies that exist, then maintain or can improve the existing advantages.